Atmosphere in the eye of Sumatran GPS Array : a case study of the Southwest Monsoon season - Zhang, Teng Fei (2017)
The thesis is a study of the zenith wet delay observed by the Sumatran GPS Array. I focused on the southwest monsoon season, and conducted a thorough analysis to identify the atmospheric processes that impact the water vapour over the GPS network. The roles of the southwest monsoon and the dry air intrusion are revealed. Furthermore, GPS devices also provide a rare chance to directly observe the high-frequency variabilities of the water vapor. The diurnal variability shows an interesting propagation. The coast reaches its diurnal peak first, and then the adjacent sea follows. The semidiurnal variability has a same phase with atmospheric tides. Atmospheric tides are the periodic variation of the air mass, and their semidiurnal variability is strong. Since water vapor is a component of the air mass, atmospheric tides can cause the diurnal variability in GPS observations. In conclusion, the GPS technology is proved to be a valid tool to study the in-depth atmospheric dynamics. With the appropriate approach, the GPS observation can not only quantify the influence of various atmospheric phenomena on the water vapor, but also provide helpful guidance for the numerical simulation and the weather forecast.